2006
DOI: 10.1186/cc5013
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Sepsis may impair mitochondrial utilization of oxygen. Since hepatic dysfunction is a hallmark of sepsis, we hypothesized that the liver is more susceptible to mitochondrial dysfunction than the peripheral tissues, such as the skeletal muscle. We studied the effect of prolonged endotoxin infusion on liver, muscle and kidney mitochondrial respiration and on hepatosplanchnic oxygen transport and microcirculation in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Sodium transport was decreased in both, hence, renal oxygen consumption factored for sodium reabsorption was increased in both. In another study in pigs with endotoxin infusion for 24 hours, renal oxygen extraction increased at 12 hours and remained persistently elevated at 24 hours [17]. In the above studies, renal oxygen utilization was increased despite a reduction in GFR and the filtered tubular load.…”
Section: Alterations In Renal Hemodynamics and Oxygenation In Aki Sepmentioning
confidence: 92%
“…Sodium transport was decreased in both, hence, renal oxygen consumption factored for sodium reabsorption was increased in both. In another study in pigs with endotoxin infusion for 24 hours, renal oxygen extraction increased at 12 hours and remained persistently elevated at 24 hours [17]. In the above studies, renal oxygen utilization was increased despite a reduction in GFR and the filtered tubular load.…”
Section: Alterations In Renal Hemodynamics and Oxygenation In Aki Sepmentioning
confidence: 92%
“…Whereas Porta et al reported no changes in skeletal muscle oxidative phosphorylation in prolonged endotoxemia (108), Trumbeckaite and Gellerich and colleagues showed significant reductions in complex I/III activity in the vastus lateralis of endotoxin-treated rabbits (109). Others have shown that, in the CLP model, sepsis decreases complex I activity and ATP levels in hind-limb muscle, mirroring previous findings reported in muscle biopsies from septic patients (77).…”
Section: Mitochondriamentioning
confidence: 99%
“…Several rodent studies that included resuscitation demonstrated hyperlactatemia despite unchanged or even increased tissue PO 2 , and this coincided with both reduced function and structural damage to mitochondria ( 74 , 82 85 ). Resuscitated models investigating higher species (cats, swine, baboons) and characterized by a normotensive and a normo- or even hyperdynamic circulation, confirmed these findings ( 20 , 86 – 89 ). In this context, studies simultaneously recording parameters of both microcirculation and cellular O 2 utilization assume particular importance: LPS-challenged, fluid-resuscitated swine showed a reduced efficiency of hepatic mitochondrial respiration despite maintained liver surface laser Doppler blood flow ( 20 ).…”
Section: Evidence For Cellular Energetic Failure Resulting From Reducmentioning
confidence: 52%
“…Resuscitated models investigating higher species (cats, swine, baboons) and characterized by a normotensive and a normo- or even hyperdynamic circulation, confirmed these findings ( 20 , 86 – 89 ). In this context, studies simultaneously recording parameters of both microcirculation and cellular O 2 utilization assume particular importance: LPS-challenged, fluid-resuscitated swine showed a reduced efficiency of hepatic mitochondrial respiration despite maintained liver surface laser Doppler blood flow ( 20 ). The same group however reported in a longer-term model, unchanged liver tissue mitochondrial resuscitation with a tendency toward enhanced microcirculatory blood flow ( 88 ).…”
Section: Evidence For Cellular Energetic Failure Resulting From Reducmentioning
confidence: 52%
See 1 more Smart Citation